ANALISIS PERSEPSI MAHASISWA TERHADAP LITERASI KEUANGAN DIGITAL DALAM PENGELOLAAN KEUANGAN PRIBADI - M. Azy Rahmanda; Sabrina Noor Wijaya; Abdul Azis; Sinta Nova; Reni Ria Armayani Hasibuan (CV. Barokah Publsiher, 2025)
The development of digital technology has driven significant transformations in the financial system, including among university students, a young age group that predominantly uses digital financial services. Students are increasingly familiar with the use of e-wallets, mobile banking, and digital investments in their daily financial activities. However, the high adoption rate of these services is not always accompanied by adequate levels of digital financial literacy. This study aims to analyze students’ perceptions of digital financial literacy and its implications for personal financial management. The research method used a qualitative approach through literature review by analyzing journal articles, books, and relevant scientific documents. The results indicate that students’ understanding of e-wallets, mobile banking, and digital investments positively influences personal financial management behaviors, such as budget planning, spending control, and saving and investment decisions. However, limited understanding of the risks, data security, and long-term consequences of using digital financial services remains a major challenge. Therefore, improving digital financial literacy that is applicative and practice-oriented is needed to support wiser and more sustainable personal financial management of students in the digital era